Literature Review: Risk of Death in Covid-19 Patients (Unnes Journal of Public Health, 2020)
Covid-19 is a contagious pulmonary infectious disease caused by a new type of coronavirus (SARS-COV-2). Covid-19 is a global pandemic that has infected millions of people and killed thousands of people in the world. Cases of death in Covid-19 patients were first discovered in China in December 2019. In Indonesia, since it was first discovered, cases of death of Covid-19 patients continue to increase and has become one of the countries with the highest fatality rate in the world reaching 9.11 percent. The purpose of this study is to determine risk factors for death in covid-19 patients in China in order to get guidance in preventing death in Covid-19 patients in Indonesia. This type of research is a literature review. The results of the study found five risk factors for death in Covid-19 patients, namely age, Covid-19 complications, the immune system (immunity), concomitant diseases (cormobidity), and treatment facilities. Suggestions of various risk factors for death in Covid-19 patients in China are expected to be a guide in efforts to prevent death in Covid-19 patients that occur in Indonesia.